Old oppressed and new oppressors: citizenship and xenophobic discourse in Phaswane Mpe’s welcome to our Hillbrow - Mohammed, Mustafa; Mohammed, Omar; Kaur, Hardev (Deanship of Academic Research, University of Jordan, 2020)
Xenophobia is documented as a grave, international collective phenomenon, it is prevalent in South Africa due to the economic and social degeneration and the static state of poverty of people after emancipation. The rise of xenophobia after the eradication of apartheid in 1994 was an outcome to the state politics of citizenship and the failure of the government to achieve the promises of democracy. Previous studies attribute xenophobia in South Africa to social and economic problems while its rise was a result to poverty and economic decay only. This article argues that the rise of xenophobia in South Africa is the outcome of the political discourse of citizenship and exclusiveness. Thus, the study aims to demonstrate that xenophobia is stimulated and triggered by state discourse of South African officials including police officers and Home Department agents drawing on Michael Neocosmos’ Citizenship reading. The article concludes that xenophobia in South Africa is triggered and maintained by the state politics and the governmental discourse. HARDEV KAUR A/P JUJAR SINGH// ALSHAJLAWI MUSTAFA MOHAMMED ABDULLAH/ Omar Mohammed